Cannabidiol, a plant-derived compound, is an emerging strategy for treating cognitive impairments: comprehensive review of randomized trials - Yndart Arias, Adriana; Vadell, Kamila; Vashist, Arti; Kolishetti, Nagesh; Lakshmana, Madepalli K.; Nair, Madhavan; Liuzzi, Juan P. (Frontiers in Pharmacology, 2024)
Background: Finding new strategies to treat cognitive disorders is a challenging task.Medication must defeat the blood-brain barrier. Cannabidiol (CBD), a non-intoxicating compound of the cannabis plant, has gained recognition as a nutraceutical for its potential effectiveness in treating anxiety, oxidative stress, convulsive, and inflammation. However, the dose, tolerable upper intake, formulation, administration routes, comorbidities, diet, and demographic factors to reverse cognitive impairments have not been completely explored. Trials using CBD as a primary intervention have been conducted to alleviate cognitive issues. This review evaluates the benefits of CBD supplementation, research design, formulations, and outcomes between those randomized clinical trials. Methods: An evidence-based systematic literature review was conducted using PUBMED and the Florida International University Research Library resources. Fourteen randomized trials were selected for review, and their design and outcomes were compared conceptually and in the form of resume tables. Results: CBD showed improvement in anxiety and cognitive impairments in 8 out of 14 analyzed trials. However, this variability could be justified due to the diversity of the trial design, underpowered studies, characteristics of the assayed population, uncontrolled results for comorbidities, medications, the severity of dependence on drugs, compliances, and adherence. Overall, oral single doses of 200 mg -1,500 mg or vaporized 13.75 mg of CBD were shown to be effective at treating anxiety and cognition. Conversely, results that did not have a significant effect on treating cognitive impairments can be explained by various factors such as THC or other abuse drugs masking effect, low dose, and unknown purity of CBD.Lastly, CBD showed a safe profile with scarce or no serious adverse events and no drug addiction behavior. Conclusion: As medical cannabis becomes more accessible and famous, it is essential to understand if medication rich in CBD exerts a beneficial effect on cognitive disorders. Our study concludes that CBD is a promising candidate for treating neurocognitive disorders; however, more studies are required to define CBD as a therapeutic candidate for managing cognitive disorders.